RB but not R‐HCVAD is a feasible induction regimen prior to auto‐HCT in frontline MCL: results of SWOG Study S1106. (19th December 2016) - Chen, Robert W.; Li, Hongli; Bernstein, Steven H.; Kahwash, Samir; Rimsza, Lisa M.; Forman, Stephen J.; Constine, Louis; Shea, Thomas C.; Cashen, Amanda F.; Blum, Kristie A.; Fenske, Timothy S.; Barr, Paul M.; et al.
Summary: Aggressive induction chemotherapy followed by autologous haematopoietic stem cell transplant (auto‐HCT) is effective for younger patients with mantle cell lymphoma (MCL). However, the optimal induction regimen is widely debated. The Southwestern Oncology Group S1106 trial was designed to assess rituximab plus hyperCVAD/MTX/ARAC (hyperfractionated cyclophosphamide, vincristine, doxorubicin and dexamethasone, alternating with high dose cytarabine and methotrexate) (RH) versus rituximab plus bendamustine (RB) in a randomized phase II trial to select a pre‐transplant induction regimen for future development. Patients had previously untreated stage III, IV, or bulky stage II MCL and received either 4 cycles of RH or 6 cycles of RB, followed by auto‐HCT. Fifty‐three of a planned 160 patients were accrued; an unacceptably high mobilization failure rate (29%) on the RH arm prompted premature study closure. The estimated 2‐year progression‐free survival (PFS) was 81% vs. 82% and overall survival (OS) was 87% vs. 88% for RB and RH, respectively. RH is not an ideal platform for future multi‐centre transplant trials in MCL. RB achieved a 2‐year PFS of 81% and a 78% MRD negative rate. Premature closure of the study limited the sample size and the precision of PFS estimates and MRD rates. However, RB can achieve a deep remission and could be a platform for future trials in MCL.